2002
DOI: 10.1111/1475-4959.00052
|View full text |Cite
|
Sign up to set email alerts
|

Decision–making and innovation among small–scale yam farmers in central Jamaica: a dynamic, pragmatic and adaptive process

Abstract: Many researchers in the Caribbean have protested the generally negative stereotyping of small-scale farmers and the small-scale domestic agricultural sector. The essence of this pejorative attitude is that small-scale farmers display apathy and resistance to change and are reluctant to accept innovations. A major reason for this perspective is a lack of knowledge and understanding of and sensitivity towards the factors that influence and inform farmers' decisions. Studying the decision-making of small-scale fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 1 publication
1
28
0
Order By: Relevance
“…Being able to depend upon the cooperative to purchase their milk regardless of how much milk is available at different times of the year and, overall, the trust that the cooperative will support their long-term objective of becoming more successful dairy farmers (see Table 5). Most important, our findings reinforce those of other researchers who have shown that the desire of smallholders to preserve their farms and local communities is not, in any way, an obstacle to adopting new innovations [23,24].…”
Section: Understanding the Role Of Income In Member Engagementsupporting
confidence: 89%
See 1 more Smart Citation
“…Being able to depend upon the cooperative to purchase their milk regardless of how much milk is available at different times of the year and, overall, the trust that the cooperative will support their long-term objective of becoming more successful dairy farmers (see Table 5). Most important, our findings reinforce those of other researchers who have shown that the desire of smallholders to preserve their farms and local communities is not, in any way, an obstacle to adopting new innovations [23,24].…”
Section: Understanding the Role Of Income In Member Engagementsupporting
confidence: 89%
“…Research has found that these farmers are rational actors, who are aware of this need and do not have any aversion to new information that will make their farming operations more sustainable [23].…”
Section: Selective Benefitsmentioning
confidence: 99%
“…Thirteen of the respondents were females and all farmers in the survey planted yams. The paper also draws on previous research in the area [6][7][8][9][10][11][12][13]. …”
Section: Study Area and Methodologymentioning
confidence: 99%
“…A more serious consideration is the viability of this system on some slopes. Farmers have argued that systems which do not use yam sticks would not work on shadowed back ridges (ubac slopes) [9].…”
Section: Planting Yams In Hills Without Stakesmentioning
confidence: 99%
“…Many studies (Feinerman and Finkelshtain 1996;Dercon 1998;Ghadim and Pannell 1999;Beckford 2002) have provided evidence that individual household members' risk preferences and their perceptions of the benefits, costs, and riskiness play a significant role in the choice of different livelihood alternatives available to them. Therefore, the individual decision to keep a given species of small ruminants was expected to be strongly affected by the risk preferences and perceived benefits associated with each species.…”
Section: Conceptual Frameworkmentioning
confidence: 99%